Conditions affecting the tourism development of a destination through visitors’ evaluation: The case of Sapa Town, Lao CAI Province, Vietnam - Phuong, Nga Nguyen Thi; Thi, Phan Trinh; Thu, Ha Nguyen Thi (International Journal of Innovative Research and Scientific Studies, 2024)
The research aims to determine the conditions that affect the tourism development of a destination through the evaluation of tourists (in the case of Sapa town, Lao Cai province, Vietnam). Using quantitative methods, the article uses SPSS software to process interview results from 400 tourists according to four groups of factors: (i) accessibility to public communication services, hotel amenities and hygiene, level of convenience and comfort of sightseeing transportation; (ii) the adequacy, capacity, and hygiene of the parking lot, the diversity and specificity of souvenirs, the attractiveness and diversity of entertainment activities, (iii) security issues, order, and safety and (iv) the quality of tourism human resources. The research results show a group of conditions, such as the adequacy, capacity, and hygiene of the parking lot, the diversity and specificity of souvenirs, and the attractiveness and diversity of entertainment activities. Location and natural landscape have the strongest impact on the development of a tourist destination. While factors in groups I, iii, and iV have a lower level of influence. From there, this study proposes policy implications for improving the service quality of the destination, such as: the issue of human resource training, the quality of infrastructure; renewing products and services, and diversifying local cultural experiences. In particular, the quality of human resources is an issue that needs improvement not only in Sapa but also for many tourist destinations in mountainous regions of Vietnam.